Visual Analysis and the application of Islamic law in farm animal vocabulary learning videos for children - Pertiwi, Annisa Bela; Budiman, Budiman; Iskandar, Asep Deni; Supandi, Fajar Persada (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2024)
This study analyzes the visual expression and application of Islamic legal principles, particularly iqtina ash-shurah, in the animated video